Information Sources Preferences of Postgraduate Students at University Level - Muhammad Yousuf; Dr. Muhammad Shahid Farooq; Muhammad Jawad (Social Science Review Archives, 2025)
The study aimed at identifying the information source preferences (ISP) of postgraduate students at University of the Punjab, Lahore (PU). The researchers investigated the differences in students’ ISP with respect to gender, GPA, level of study, locale and use of social media. Population of the study comprised postgraduate students of PU. 330 postgraduate students were selected as the population of study using Yamane formula with margin of error of 0.05. Descriptive research design was applied. Information Seeking Behavior Questionnaire (ISBQ) was used to collect data and was analyzed using statistical software. Firstly, information source preference was analyzed as general then differences were measured based on demographic variables through frequencies, means, percentages, t-test, and one-way ANOVA. Most preferred information source was Journal Articles (Mean=4.69) as 71.5% students always consult and 26.1% often consult Journal Articles followed by Books (Mean=4.20) and Conference Proceeding (Mean=4.13). It also found that Encyclopedia was not much preferred by the postgraduate students (Mean=3.37). The PhD scholars were slightly behind than MPhil scholars in consulting Books, Theses & Dissertations and Reports. It is recommended to provide training sessions to the PhD scholars and postgraduate students with backgrounds from private institutions on relevant and updated information sources.